Τhe complete mitochondrial genomes of Ceratitis rosa and Ceratitis quilicii, members of the Ceratitis FAR species complex (Diptera: Tephritidae). Issue 3 (4th March 2021) - Drosopoulou, Elena; Damaskou, Aristi; Markou, Angeliki; Ekesi, Sunday; Khamis, Fathiya; Manrakhan, Aruna; Augustinos, Antonios A.; Tsiamis, George; Bourtzis, Kostas
Abstract: Ceratitis FAR is an African species complex comprising insect pests of great economic interest and obscure species limits. Here, we report the mitochondrial genomes of two members of the FAR complex, namely Ceratitis rosa and the recently characterized Ceratitis quilicii . A phylogenetic analysis based on PCGs of available Tephritidae mitogenomes is presented. The current mitochondrial sequences from the FAR complex could contribute toward the resolution of phylogenetic relationships and species limits within this taxonomically challenging group, which is also an important issue for the development of environment-friendly and species-specific control methods, such as the sterile insect technique (SIT).